Single-degree-of-freedom based pressure-impulse diagrams for blast damage assessment - Syed, Zubair Imam; Liew, Mohdshahir; Hasan, Muhammad Hasibul; Venkatesan, Srikanth (Trans Tech Publications Ltd, 2014)
Pressure-impulse (P-I) diagrams, which relates damage with both impulse and pressure, are widely used in the design and damage assessment of structural elements under blast loading. Among many methods of deriving P-I diagrams, single degree of freedom (SDOF) models are widely used to develop P-I diagrams for damage assessment of structural members exposed to blast loading. The popularity of the SDOF method in structural response calculation in its simplicity and cost-effective approach that requires limited input data and less computational effort. The SDOF model gives reasonably good results if the response mode shape is representative of the real behaviour. Pressure-impulse diagrams based on SDOF models are derived based on idealised structural resistance functions and the effect of few of the parameters related to structural response and blast loading are ignored. Effects of idealisation of resistance function, inclusion of damping and load rise time on P-I diagrams constructed from SDOF models have been investigated in this study. In idealisation of load, the negative phase of the blast pressure pulse is ignored in SDOF analysis. The effect of this simplification has also been explored. Matrix Laboratory (MATLAB) codes were developed for response calculation of the SDOF system and for repeated analyses of the SDOF models to construct the P-I diagrams. Resistance functions were found to have significant effect on the P-I diagrams were observed. Inclusion of negative phase was found to have notable impact of the shape of P-I diagrams in the dynamic zone. © (2014) Trans Tech Publications, Switzerland.